Model Pembelajaran Sejarah Berbasis Pemikiran Soekarno untuk Meningkatkan Sikap Kepemimpinan Siswa di SMAN 11 Medan - Kurnia A Daulay; Rani Sulistiawati; Romian Sihite; Qoriatul Kahfi (UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to develop a historical learning model based on Soekarno's thinking to improve students' leadership attitudes. Soekarno is known as the founding father of the Indonesian nation whose leadership both before and after Indonesia's independence.. The form of this research is research on the development of learning models (R&D) from the ADDIE model. The results showed that the results of the effectiveness of Sukarno's thinking-based learning model combined with existing learning approaches and models, showed that the experimental class had better results than the control class. This is indicated by the average test results for the control class, namely the pre-test 37.77 and the post-test 65.92. While the T-test was 6.983 with a significance level of 0.000 <0.25, while the average test results for the experimental class were 33.66 pre-test and 72.33 post-test. While the T test is 122,058 with a significance level of 0.000 <0.25. The average test results for the control class were 95.66 before treatment and 98.85 after treatment. While the T-test is 5.135 with a significance level of 0.000 <0.025, while the average test results for the experimental class are 98.20 before treatment and 1.003 after treatment. While the T-test is 4.267 with a significance level of 0.000 <0.025.